Sign and size asymmetries between futures and spot prices in the markets of agricultural commodities - Dimitrios Panagiotou (Modern Finance)
The goal of the present article is to examine asymmetries in sign and size among spot and futures prices in the markets of agricultural commodities of corn, hard red wheat, and soybeans. Daily observations of spot and futures prices for the three agricultural commodities and the econometric tool of local linear regressions have been utilized. The empirical results were obtained for the period between January 2000 and the end of March 2025. The empirical results reveal evidence of asymmetric dependence in sign and size, at the very extremes of the distribution, under extreme negative changes for the commodity of corn and under extreme positive changes for the commodity of soybeans. Accordingly, extreme price increases/decreases of different signs but of the same absolute magnitude are transmitted from futures to spot prices with different intensity. Moreover, large price shocks in value are transmitted from futures to spot prices more forcefully compared to smaller ones. Evidence of sign and size asymmetries might greatly help diversify the traders’ investment risk.